Analysis of the Application of Income Tax Article 21 on Employee Salaries at the Panambungan Health Center Makassar City - Ekawati Febrianti Umafagur; Tenriwaru; Fifi Nurafifah Ibrahim; Rastina Kalla (www.amertainstitute.com, 2025)
This study aims to analyze the calculation, withholding, and reporting of Income Tax Article 21 on the income of permanent employees at the Panambungan Health Center, as well as to assess its compliance with applicable tax regulations. The research method used is quantitative descriptive with a qualitative approach. Data were obtained through interviews with financial staff (treasurer) and documentation of withholding slips and employee salary data. The results of the study indicate that the calculation of Income Tax Article 21 at the Panambungan Health Center is not fully in accordance with tax regulations, particularly in the use of non-taxable income (PTKP), which does not take into account each employee's dependent status. This has resulted in excessive tax withholdings (overpayments). The withholding is carried out using the gross-up method; however, there are still technical errors in the calculation. Meanwhile, the reporting of Income Tax Article 21 has been carried out in accordance with the regulations through e-filing, although the withholding slips are only provided annually, not monthly.